Estimation of cruciate ligament forces via smart compression garments - Belbasis, A.; Fuss, F. K.; Sidhu, J. (Procedia Engineering, 2015)
Muscle and ligament injuries are among the most common sports injuries with Anterior Cruciate Ligament (ACL) injuries commonplace in many sporting codes. Several studies have been performed in an effort to quantify the loading of the cruciate ligaments during activity. However these ultimately rely on data obtained through static machines performing isokinetic movements. Smart Compression Garments (SCG), functioning as a wearable muscle and ligament management system, were developed to understand the loading of the ligaments whilst providing an additional means to mitigate the risk of overload and strain. Forces were determined through a new method of calculating the cruciate ligament forces utilising the forward dynamic calculation of the SCG determined muscle forces and knee angle. Four controlled scenarios were performed to evaluate the ligament loading conditions involving maximal contraction of the hamstrings or quadriceps at several knee flexion angles. The loading of the cruciate ligaments was demonstrated during walking on a treadmill, where the both the ACL and PCL were significantly stressed alternatively once per stride. The application of an SCG allows for the associated information processing of soft tissue data through a wearable system capable of assessing active muscle load, cruciate ligament forces, and co-contraction of paired muscles in real-time, providing metrics for improved performance and safety.